2010
DOI: 10.1007/s10585-010-9352-x
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal mode of migration participates in pulmonary metastasis of mouse osteosarcoma LM8

Abstract: The outcomes of osteosarcoma patients still remain poor because of intractable pulmonary metastasis. We previously established a highly metastatic osteosarcoma cell line, LM8 from Dunn mouse osteosarcoma by in vivo selection. We herein aimed to clarify the characteristic biological features related with high metastatic potential and new target molecules to suppress pulmonary metastasis of osteosarcoma, using this syngeneic spontaneous metastatic model. LM8 cells acquired fibroblastic morphology with striking f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 37 publications
3
43
0
Order By: Relevance
“…26 These findings strongly suggest that PP2A Cα has an important role in the acquisition of distinct cell morphology in LM8 cells. In addition, LM8 cells display higher levels of FAK phosphorylation at focal adhesion sites, 8 which has key roles in cell migration and metastasis of tumor ) Cells were exposed to serum-free medium for the indicated periods and the collected cell lysates were subjected to western blot analysis using specific antibodies. The cleaved forms of caspase-3 and PARP are pointed by the arrow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 These findings strongly suggest that PP2A Cα has an important role in the acquisition of distinct cell morphology in LM8 cells. In addition, LM8 cells display higher levels of FAK phosphorylation at focal adhesion sites, 8 which has key roles in cell migration and metastasis of tumor ) Cells were exposed to serum-free medium for the indicated periods and the collected cell lysates were subjected to western blot analysis using specific antibodies. The cleaved forms of caspase-3 and PARP are pointed by the arrow.…”
Section: Discussionmentioning
confidence: 99%
“…6 LM8 cells were also reported to possess activated focal adhesion kinase (FAK) and high NF-κB activity. 7,8 Therefore, LM8 cells could be a useful tool to study the mechanisms involved in proliferation and metastasis of osteosarcoma.…”
mentioning
confidence: 99%
“…Single migration consists of two alternative mechanisms of migration, namely amoeboid and mesenchymal migration (45). According to a report by Yui et al (46), acquisition of the mesenchymal mode of migration is critical in pulmonary metastasis of OS, which is mesenchymal in origin. This report also demonstrated that Rho-associated kinase (ROCK) inhibitor increases OS cell migration with induction of migration mode from amoeboid to mesenchymal (46).…”
Section: Discussionmentioning
confidence: 99%
“…According to a report by Yui et al (46), acquisition of the mesenchymal mode of migration is critical in pulmonary metastasis of OS, which is mesenchymal in origin. This report also demonstrated that Rho-associated kinase (ROCK) inhibitor increases OS cell migration with induction of migration mode from amoeboid to mesenchymal (46). PKD1 is activated by RhoA via ROCK, which has a serine/threonine domain (47), and Matsumoto et al reported that highly activated Rho-ROCK pathway inhibited OS cell invasion and migration with decreasing MMP2 activity (48).…”
Section: Discussionmentioning
confidence: 99%
“…Note Yui et al (2010) developed a highly metastatic osteosarcoma cell line through in vivo selection which, in comparison with the parental line, demonstrated higher levels of activated FAK and cdc42. Hanada et al (2005) showed localization of phosphorylated FAK at the infiltrative edge in a three dimensional culture model using invasive murine fibrosarcoma cells.…”
Section: Soft Tissues Bone and Hematolymphoid Tissuesmentioning
confidence: 99%